Prominent Precession Band Variance in ENSO Intensity Over the Last 300,000 Years - Zhengyao Lu; Zhengyu Liu; Guangshan Chen; Jian Guan (Geophysical Research Letters)
Abstract Three transient National Center for Atmospheric Research Community Climate System Model, version 3 model simulations were analyzed to study the responses of El Niño–Southern Oscillation (ENSO) and the equatorial Pacific annual cycle (AC) to external forcings over the last 300,000 years. The time‐varying boundary conditions of insolation, greenhouse gases, and continental ice sheets, accelerated by a factor of 100, were sequentially added in these simulations. The simulated ENSO and AC amplitudes change in phase, and both have pronounced precession band variance (~21,000 years). The precession‐modulated slow (orbital time scales) ENSO evolution is dominated linearly by the change of the coupled ocean‐atmosphere instability, notably the Ekman upwelling feedback and thermocline feedback. In contrast, the greenhouse gases and ice sheet forcings (~100,000‐year cycles) are opposed to each other as they influence ENSO variability through changes in AC amplitude via a common nonlinear frequency entrainment mechanism. The acceleration technique could dampen and delay the precession signals below the surface ocean associated with ENSO intensity.